2017
DOI: 10.1080/14767058.2017.1319923
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic profile of serum of pregnant women carring a fetus with Down syndrome using nano uplc Q-tof ms/ms technology

Abstract: We found a different serum protein profile in mothers carrying DS fetuses that do not reflect expression of genes in the extra chromosome. Further studies will be necessary to establish the role of these proteins in aneuploid fetus and analyze their possible use as potential biomarkers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Proteomic results are constantly changing, showing how sets of proteins interact with environmental factors [ 40 ]. Furthermore, the concentrations of many proteins depend on their locations in biological compartments and the phase of the cell cycle, which can also be interrupted by many diseases [ 41 , 42 ]. In the results described above, we see differences depending on the selected research group and control group.…”
Section: Markers In the Tears Of Patients With Graves’ Orbitopathymentioning
confidence: 99%
“…Proteomic results are constantly changing, showing how sets of proteins interact with environmental factors [ 40 ]. Furthermore, the concentrations of many proteins depend on their locations in biological compartments and the phase of the cell cycle, which can also be interrupted by many diseases [ 41 , 42 ]. In the results described above, we see differences depending on the selected research group and control group.…”
Section: Markers In the Tears Of Patients With Graves’ Orbitopathymentioning
confidence: 99%
“…Proteomics could also enable the detection of novel and more affordable T21 biomarkers [ 68 , 69 ]. Accordingly, Charkiewicz et al suggested that imbalance in the level of circulating proteins in maternal blood can stimulate an immune response producing autoantibodies.…”
Section: Proteomics and Down Syndrome Screeningmentioning
confidence: 99%
“…At the same time, proteomic results showing how sets of proteins interact with environmental factors are constantly changing [ 85 ]. Furthermore, the concentrations of many proteins depend on their locations in biological compartments and the phase of the cell cycle, which can also be interrupted by many diseases [ 68 , 69 ]. However, the extensive software required for utilizing proteomic data and the need for highly proficient technicians substantially increase the cost.…”
Section: Proteomics and Down Syndrome Screeningmentioning
confidence: 99%
“…We thus surveyed the proteomics literature to ascertain whether Cpn10 (or Hsp10) was actually present in human pregnancy serum. In 6 studies [21][22][23][24][25] only one study identified one Hsp10 peptide [26], although 100-800 other proteins were identified in these studies. Hsp10 is not intrinsically difficult to detect by mass spectroscopy [27,28].…”
mentioning
confidence: 99%